Intravenous fluid resuscitation : surveillance of penetrating injury in the pre-hospital environment - Zalgaonker, Mustafa (Cape Peninsula University of Technology, 2018)
Physical injury is a major cause of premature death and disability worldwide (WHO, 2015). Mortality statistics for South Africa indicate that approximately half of all injury-related deaths were intentionally inflicted, often as a result of sharp-force injuries (Donson 2009). Cape Town is reputed to be a violent city (Nicol et al., 2014). Pre-hospital emergency care providers are often the first medical contact for injured patients. Previously, it was understood that high volume crystalloid administration would improve survival and was standardised in the management of shock (Santry & Alam 2010). However, over-administration of crystalloid fluid can cause patient harm by potentially worsening injuries and can be detrimental to a patients survival. Current evidence supports the practice of lower volume crystalloid intravenous fluid administration- permissive hypotension. Little is known about pre-hospital emergency care providers intravenous fluid management practices for penetrating injury. Injury surveillance data for victims of penetrating injury is also scarce with the majority of current data taken from mortality sources. Surveilling pre-hospital cases may yield opportunities for prevention from premature mortality and morbidity. The aim of this study is to undertake surveillance of penetrating injury and related intravenous fluid resuscitation in the pre-hospital emergency care environment. A prospective observational descriptive survey was conducted in the Cape Metropole1. Over three consecutive months, emergency care providers documented parameters related to mechanism of injury, scene vital signs, hospital vital signs, intravenous fluid resuscitation and basic patient demographic information for patients with penetrating injury. A predetermined inclusion and exclusion criteria was used to sample patients.
Thesis (Master of Emergency Medical Care)--Cape Peninsula University of Technology, 2018.
Keywords: Emergency medicine; Emergency medical services; Intravenous therapy; Wounds and injuries -- Treatment